Knowledge level and self-efficacy in student preparedness for megathrust earthquake: A correlation study - Feri Ekaprasetia; Rifqotul Inayat; Moh. Wildan; Sugijati Sugijati (Yayasan Pendidikan Kardin Assidiq, 2025)
Background: Megathrust earthquakes are natural disasters with the potential to cause severe damage and significantly impact people's lives, especially in earthquake-prone areas such as Puger, Jember. Schools, as places where many students gather during school hours, are highly vulnerable to disasters such as earthquakes, floods, and landslides, which can cause building collapse and endanger student safety. Purpose: This study aims to examine the relationship between knowledge and preparedness, and self-efficacy, with students' preparedness for a megathrust earthquake in the Puger area. Methods: The study used a quantitative approach with a cross-sectional correlational design. The sampling technique used cluster random sampling followed by random sampling within each designated cluster. Data analysis used the Spearman Rank correlation test. Results: The results showed a significant relationship between knowledge and preparedness (p = 0.000) and between self-efficacy and preparedness (p = 0.012). This means that increasing knowledge and self-efficacy can significantly improve student preparedness. Conclusion and recommendation: There is a positive and significant relationship between knowledge level and preparedness, and self-efficacy and preparedness among students at SMPN 3 Puger.